Notificação de violência contra criança: conhecimento e comportamento dos profissionais de saúde - Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Costa, Adriana Cristina Oliva [UNESP]; Queiroz, Ana Paula Dossi de Guimarães e [UNESP] (My University, 2011)
Introduction: The violence against children and teenagers severely damages physical health and psychological development of their victims. Health professionals are in a strategic position to detect cases of assault and legally obliged to report such cases, even suspected. Objectives: This study aimed to assess the knowledge of health professionals who work in the National Health System (SUS) on reporting of violence against children and adolescents. Methods: We conducted interviews with 54 primary care team of four cities from the region of São José do Rio Preto. Results: Through the study could be seen that 92.6% of respondents suspected or witnessed violence against children exercising their profession in the SUS. About Order 1968/2001, 75.5% of practitioners claim ignoring it. 96.2% were not informed about completing the notification form of violence. 88.9% do not know about the existence of the same workplace. The association between obtaining information on work and the act of notification was significant (p = 0.0276). Conclusion: The professionals are still unaware of the legal issues related to notification. It is suggested that the training of them to deal with the bureaucratic side of the issue, once notify contributes to the delineation of the epidemiology of violence and consequent development of public policies

Introdução: A violência contra crianças e adolescentes prejudica severamente a saúde física e o desenvolvimento psicológico de suas vítimas. Os profissionais de saúde estão em posição estratégica para detectar situações de agressão e têm obrigação legal de notificar esses casos, ainda que suspeitos. Objetivos: Este estudo teve por objetivo avaliar o conhecimento dos profissionais da saúde que atuam no Sistema Único de Saúde (SUS) sobre notificação de violência contra crianças e adolescentes. Metodologia: Realizou-se entrevista com 54 profissionais da atenção básica de quatro municípios pertencentes à Região de São José do Rio Preto-SP. Resultados: Por meio do estudo, pôde-se constatar que 92,6% dos entrevistados suspeitaram ou presenciaram violência contra crianças ao exercerem sua profissão no SUS. Sobre a Portaria no1.968/2001, 75,5% dos profissionais alegam desconhecê-la e 96,2% não foram orientados sobre o preenchimento da ficha de notificação de violência. Constatou-se que 88,9% não sabem informar sobre a existência dessa ficha no local de trabalho. A associação entre a obtenção de informações no trabalho e o ato de notificar mostrou-se significante (p=0,0276). Conclusão: Os entrevistados ainda desconhecem os aspectos legais relacionados com a notificação. Sugere-se a capacitação desses profissionais para lidar com a face burocrática do assunto, uma vez que notificar contribui para o delineamento do perfil epidemiológico da violência e para o consequente desenvolvimento de políticas públicas.
Reporting of violence against children: knowledge and behavior of health professional
Keywords: Violence; Health manpower; Mandatory reporting; Violência; Recursos humanos em saúde; Notificação de abuso